2013
DOI: 10.1021/la402788a
|View full text |Cite
|
Sign up to set email alerts
|

Hollow Colloidosomes Prepared Using Accelerated Solvent Evaporation

Abstract: We demonstrate a new, scalable, simple, and generally applicable two-step method to prepare hollow colloidosomes. First, a high volume fraction oil-in-water emulsion was prepared. The oil phase consisted of CH2Cl2 containing a hydrophobic structural polymer, such as polycaprolactone (PCL) or polystyrene (PS), which was fed into the water phase. The water phase contained poly(vinylalcohol), poly(N-isopropylacrylamide), or a range of cationic graft copolymer surfactants. The emulsion was rotary evaporated to rap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 28 publications
(74 reference statements)
0
9
0
Order By: Relevance
“…The DCM dissolves in water, leading to precipitation of the PLA on the tetradecane droplets. Also polycaprolactone or polystyrene (Shahidan et al 2013) and poly(lactic-coglycolic acid)-based Hemar 2009). Spray drying will result in a high quality product when the heat and mass transfer processes are well controlled, which in general is very well feasible.…”
Section: Methods Using Phase Separationmentioning
confidence: 99%
“…The DCM dissolves in water, leading to precipitation of the PLA on the tetradecane droplets. Also polycaprolactone or polystyrene (Shahidan et al 2013) and poly(lactic-coglycolic acid)-based Hemar 2009). Spray drying will result in a high quality product when the heat and mass transfer processes are well controlled, which in general is very well feasible.…”
Section: Methods Using Phase Separationmentioning
confidence: 99%
“…Moreover, increasing the particle concentration from 2 to 3 wt % produced visibly less porous colloidosomes as judged by SEM. A slightly different approach was described by Shahidan et al 51 Here either poly( -caprolactone) or polystyrene was precipitated onto a polymeric surfactant-stabilized dichloromethane-in-water emulsion, forming a particle shell during dichloromethane evaporation. One advantage of this strategy is that the colloidosome cores fill up with water after all the dichloromethane is evaporated, thus directly producing a w/w colloidosome without requiring centrifugal transfer.…”
Section: Polymerization After Pickering Emulsion Formationmentioning
confidence: 99%
“…The formulation for PHB colloidosomes started from the optimized PCL(1.5)/PVA13k(1.2) system (Entry 1 in Table 1) reported in previous study by Shahidanet al [8]. Fig.1 shows that PHB has the potential to be prepared as colloidosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The work on colloidosomes was first reported by Velev and colleagues in 1996 [2] although the term was introduced later by Dinsmore et al [1].This hollow particle plays significant roles in microencapsulation: a process in microscopic formation of thin coatings of wall material around an active ingredient [3] This process has been used in varies applications such as controlled release of drugs [4], aroma [5], food industries [6] and protection of biologically active species [7]. Microcapsules preparation methods can takes several steps which might be complex, time consuming and in need of binders [1,8]. A study by Thompson et al [9] reported that latex colloidosomes prepared via thermal annealing might be unfavorable to thermal sensitive active ingredient such as fragrances or drugs.…”
Section: Introductionmentioning
confidence: 99%